The citizen participation.: The creation of the Belo Horizonte Council of Culture (ARQUISUR Revista, 2014)
The present article is an attempt of analysing critically the experience of requesting the law enforcement, revision, implementation and election in the Belo Horizonte Council of Culture, from the decision to make the 2008 law go into effect, in 2011. Based on the understanding of what a strategic urban planning is, we will elaborate our considerations about the process experienced in the capital of Minas Gerais. The text, which is written in the third person, will be affected by our participation during the report, being finalized in the first person.
Keywords: urban culture; public politic; creative resistanc